Cell type‐specific nuclear pores: a case in point for context‐dependent stoichiometry of molecular machines - Alessandro Ori; Niccolò Banterle; Murat Iskar; Amparo Andrés‐Pons; Claudia Escher; Huy Khanh Bui; Lenore Sparks; Victor Solis‐Mezarino; Oliver Rinner; Peer Bork; Edward A Lemke; Martin Beck (Molecular Systems Biology)
Abstract To understand the structure and function of large molecular machines, accurate knowledge of their stoichiometry is essential. In this study, we developed an integrated targeted proteomics and super‐resolution microscopy approach to determine the absolute stoichiometry of the human nuclear pore complex (NPC), possibly the largest eukaryotic protein complex. We show that the human NPC has a previously unanticipated stoichiometry that varies across cancer cell types, tissues and in disease. Using large‐scale proteomics, we provide evidence that more than one third of the known, well‐defined nuclear protein complexes display a similar cell type‐specific variation of their subunit stoichiometry. Our data point to compositional rearrangement as a widespread mechanism for adapting the functions of molecular machines toward cell type‐specific constraints and context‐dependent needs, and highlight the need of deeper investigation of such structural variants.